A alegoria: um berçário de metáforas - Cardoso, Maurício Moreira (2016)
This article materializes the discussion about the relation between allegory and metaphor. Thus, it was analyzed the notion of allegory as the result of a cluster of metaphors, for, then, postulate that such a cluster is fundamentally organized by a metaphor which is set up in the level of the text as a whole. The theoretical bases are from the following scholars: Lakoff e Johnson (1999), Moisés (1999), Furniss (1997) and Hansen (2006). We come to the conclusion, considering the corpus we analyzed, that an allegory can be transformed in terms of a conceptual, complex metaphor.